2020
DOI: 10.1111/lam.13379
|View full text |Cite
|
Sign up to set email alerts
|

Identification and iterative combinatorial mutagenesis of a new naringinase‐producing strain,Aspergillus tubingensisMN589840

Abstract: Naringinase was mainly obtained by microbial fermentation, and mutagenesis was a major way for obtaining excellent mutants. The aim of this study was to screen out a high naringinase yielding mutant to enhance the potential application value of its industrialization and compare the effects of different mutagenic methods on the enzyme activity of the strain. A novel producing naringinase strain, Aspergillus tubingensis MN589840, was isolated from mildewed pomelo peel, later subjected to mutagenesis including UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous study revealed that combined multiple mutagenesis strategy (e.g., UV mutagenesis, ARTP, or ALE) had higher efficiency than that of a single one [ 59 , 60 ]. In addition, the combination of ARTP mutagenesis and ALE has been successfully applied to breed desired phenotype of strains [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous study revealed that combined multiple mutagenesis strategy (e.g., UV mutagenesis, ARTP, or ALE) had higher efficiency than that of a single one [ 59 , 60 ]. In addition, the combination of ARTP mutagenesis and ALE has been successfully applied to breed desired phenotype of strains [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…To address the bottleneck of reduced relative l ‐serine yield, Zhang et al, 106 performed ARTP mutagenesis based on engineered modified Corynebacterium glutamicum , which was found to substantially enhance l ‐serine yield. In addition, Xia et al, 107 performed mutagenesis with UV, ARTP, and UV‐ARTP, respectively, and found that the mutagenesis efficiency of UV‐ARTP was higher than that of a single ARTP and all were superior to that of UV (The yields of target products were increased by 79.08%, 123.56%, and 206% after UV, ARTP, and UV‐ARTP mutagenesis, respectively).…”
Section: Artp Mutagenesis In Synergy With Other Technologies and Scre...mentioning
confidence: 99%
“…For instance, naringinase, an enzyme with wide applications in the food, beverage, and pharmaceutical industries, saw significant productivity increases through UV-ARTP mutagenesis in Aspergillus tubingensis MN589840. High-yield mutants U1, A6, and UA13 exhibited impressive productivity enhancements [ 88 ]. Furthermore, ARTP has been successfully utilized for the production of diverse bioenzymes, including tannase [ 89 , 90 ], raw starch-degrading enzymes [ 91 ], thermostable xylanase [ 92 ], cellulose [ 93 , 94 ] and L-asparaginase [ 95 ].…”
Section: Application Of Artp To Fungimentioning
confidence: 99%